Pharmacological Preconditioning Using Diazoxide Regulates Store-Operated Ca2 + Channels in Adult Rat Cardiomyocytes - Sampieri, Raúl; Fuentes, Eridani; Carrillo, Elba D.; Hernández, Ascención; García, María C.; Sánchez, Jorge A. (Frontiers in Physiology, 2020)
Voltage-dependent Ca2+ channels and store-operated Ca2+ channels (SOCs) are the major routes of Ca2+ entry into mammalian cells. We previously reported that pharmacological preconditioning (PPC) leads to a decrease in the amplitude of Cav1.2 channel currents in the heart. In this study, we examined the changes in SOC function induced by PPC. We measured adult cardiomyocyte membrane currents using the whole-cell patch-clamp technique. In addition, we evaluated reactive oxygen species (ROS) production and intracellular Ca2+ levels in cardiomyocytes using fluorescent probes. Diazoxide was used to induce PPC, and depletion of internal stores of Ca2+ was achieved using thapsigargin. Store depletion generated inward currents with strong rectification, which were suppressed by the SOC blocker GSK-7975-A. These currents were completely abolished by PPC, an effect that was largely prevented by 5-hydroxydecanoate, a selective mitochondrial ATP-sensitive K+ channel blocker, or an intracellular mitochondrial energizing solution. Buffering of ROS and intracellular Ca2+ with N-acetylcysteine and BAPTA-AM, respectively, also prevented the effects of PPC on SOC currents. Refilling of intracellular stores was largely suppressed by PPC, as determined by measuring intracellular Ca2+ using a Fura-2 acetoxymethyl ester. These results indicate that influx of Ca2+ through SOCs is inhibited by their ROS and Ca2+-dependent inactivation during PPC and that downregulation of SOCs by PPC may play a role in cardioprotection following ischemia-reperfusion.